Proposed reference intervals of serum insulin-like growth factor-1 (IGF-1) levels in older Japanese populations - Tsuyoshi Isojima; Akira Shimatsu (Endocrine Journal)
Measurements of serum insulin-like growth factor 1 (IGF-1) levels are useful surrogate markers for the diagnosis and management of patients with growth hormone-related disorders. We have previously published normative data of serum IGF-1 levels for the Japanese population aged 0–77 years by combining and analyzing previously reported references, which were separately and independently constructed, to properly reflect data in the transition period. Although the reference is widely used in both clinical and research settings, the reference did not include data for those aged >77 years, raising the question of how we would evaluate patients over those ages. In this study, we extended the age- and sex-specific reference ranges of serum IGF-1 levels to the age of 80 years by reanalyzing combined data on serum IGF-1 levels from previously published references. Based on our results, we proposed that individuals aged >80 years can be evaluated using the references set at the age of 80 years. However, our proposal was based on a very limited number of participants. Therefore, physicians should exercise caution when interpreting IGF-1 standard deviation scores for those aged >80 years because they are not exactly correct but acceptable.